The Potentialities of Extremophiles from Hypersaline Habitats: A Review - Olukunle, Oluwatoyin Folake; Oyegoke, T. S. (European Journal of Applied Sciences, 2024)
Extremophiles are organisms that are capable of living in extreme environments (radiation, temperature, pH, salinity etc). Fascinating questions on the potentialities of extremophiles from hypersaline habitats are yet to be fully answered. Hence, it is an intriguing study that needs continuity. Most recent studies, on extremophiles, reveal the intrinsic benefits of halophiles in many biological and biotechnological processes ranging from several medical applications to a wide variety of industrial processes. In most cases, the applications of these extremophilic microorganisms and their metabolites (e.g. enzymes, inhibitors, compatible solutes, etc) in biotechnology have been the driving force to understanding these organisms, and have contributed immeasurably to several biological types of research. Despite the justifications from several studies on the potentialities of extremophiles, relatively little information is still provided on the biotechnological applications of halophiles, hence the optimal capabilities of these diverse populations of microorganisms remain clandestine and need to be explored. This review is aimed at discussing recent applications of extremophiles from hypersaline environments in order to provide a basis for researchers to explore these halophilic organisms for newer applications in many fields such as in agriculture, pharmaceuticals, medicine, food, and industries.